Highly Crumpled Boron Nitride Nanosheets as Adsorbents: Scalable Solvent‐Less Production. Issue 3 (20th January 2015) - Lei, Weiwei; Liu, Dan; Chen, Ying
<x xml:space="preserve">Abstract</x> Boron nitride nanosheets (BNNSs), so‐called "white graphene", have recently received increasing attention, both theoretically and experimentally. Although many synthetic procedures have been proposed for the synthesis of BNNSs, finding a simple, solvent‐less, catalyst‐free, and large‐scale production route is still a challenge. Here, a facile, solvent‐less, low cost, and high yield process is developed, in which mechanical solid‐state exfoliation allows scalable production of crumple BNNSs from commercial BN powders with a high surface area. Importantly, these BNNSs show unprecedentedly high adsorption of proteins described by various adsorption isotherms and kinetics models. In addition, the saturated BNNSs exhibit excellent recyclability, and maintain a high sorption capacity even after five cycles through simply regeneration process of heating in air. This easy recyclability route further demonstrates the great potential of BNNSs for water cleaning application.